IMPLEMENTASI AKAD IJARAH DALAM PRAKTIK SEWA MENYEWA POHON MANGGA MENURUT PERSPEKTIF TEORI AL-MASLAHAH - Rajiman, Arman; Iswandi, Irvan; Fitri, Ahmad Asrof (Journal of Islamic Studies, 2023)
Lease of mango trees in Haurgeulis village is carried out when mango fruit collectors need certainty of the availability of mangoes when the fruit season arrived and as well as the financial need of the owner of the mango tree. This study is categorized as field research with descriptive qualitative approach, data collection methods using observation, interviews, and documentation. In this study, the researchers choose the type of purposive sampling to determine respondents. Additionally, the analysis follows some steps: data checking, classification, verification, analysis, and making conclusion. The result of the study shows that: 1. The implementation Ijarah contract of the lease of mango tree is carried out verbally, the contract is carried out simultaneously when the lessee pay a lease fee to the mango tree owner accompanied by a limitation on the lease period in accordance with the agreement of both parties; 2. The practice of Ijarah contract of the lease of mango tree which has been carried out in the perspective of al-maslahah theory has brought benefits to both the tree owner and the lessee at the level of al-maslahah dharuriyah, although in certain circumstances the lessee has the potential to suffer losses, this is just a risk in business.